Asas Legalitas dalam Perspektif Filsafat Hukum: Kajian Perbandingan Asas Legalitas Indonesia dan Prancis - Faqihisyam Irfandy; Ferly Amlizyan; Rusmilawati Windari (Jurnal Hukum, Administrasi Publik dan Negara, 2025)
This study aims to describe the principles of legality in Indonesia and France. This study uses normative legal research methods, namely secondary legal materials in the form of data obtained from books and opinions of experts related to this study. The results of this study indicate that the principles of legality in Indonesia and France highlight the importance of legal certainty, human rights, and a sense of justice in the criminal law system. In Indonesia, the principle of legality has been regulated in the Criminal Code since 1946, but its application is often not pure because of the customary law that still applies. Although there have been amendment efforts, it often ends in a confusing system. Meanwhile, in France, the principle of legality developed from resistance to arbitrary power, which was emphasized in the Habeas Corpus Act in England in 1679. This principle gives parliament the authority to determine the components of violations and their sanctions, as a guarantee of the freedom of citizens from excessive tyrannical actions.